Fungal network composition and stability in two soils impacted by trifluralin - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Xu, Huifang; Zheng, Xiaoke; Zhang, Changpeng; Du, Pengqiang (Frontiers in Microbiology, 2023)
In this study, two agricultural soils was used to test the impact of trifluralin on fungal network. Two soils were treated with trifluralin (0, 0.84, 8.4, and 84 mg kg–1) and kept in artificial weather boxes. Under the impact of trifluralin, the fungal network nodes, edges, average degrees were increased by 6-45, 134-392, and 0.169-1.468 in two soils, respectively; however, the average path length was decreased by 0.304-0.70 in both soils. The keystone nodes were also changed in trifluralin treatments in two soils. In two soils, trifluralin treatments shared 219-285 nodes and 16-27 links with control treatments, and the network dissimilarity was 0.98-0.99. These results indicated that fungal network composition was significantly influenced. After trifluralin treating, fungal network stability was increased. Specifically, the network robustness was increased by trifluralin with 0.002-0.009, and vulnerability was decreased by trifluralin with 0.0001-0.00032 in two soils. Fungal network community functions were also impacted by trifluralin in both soils. Totally, trifluralin significantly impacts fungal network.